I can not figure out why this is false????
Find a formula for the sum y³?+y³?+?+y??.
y³?+y³?+?+y??=(1+y+?+y³³)+(y³?+y³?+?+y??)-(1+y+?+y³³)
=(1+y+?+y??)-(1+y+?+y³³)=((y??-1)/(y-1))-((y³?-1)/(y-1))
Check: Evaluate ?_{i=34}??y^{i} = {
-((y³?)/(y-1))+((y??)/(y-1)) if y?1
44 if y=1
?
-((y³?)/(y-1))+((y??)/(y-1))=((y??-1)/(y-1))-((y³?-1)/(y-1)) is true
Using factoring:
y³?+y³?+?+y??=y³?(1+y+y²+?+y?³)=y³?(((y??-1)/(y-1)))
Check: Evaluate ?_{i=34}??y^{i}= {
-((y³?)/(y-1))+((y??)/(y-1)) if y?1
44 if y=1
?
-((y³?)/(y-1))+((y??)/(y-1))=y³?(((y??-1)/(y-1))) is false
Find a formula for the sum y³?+y³?+?+y??.
y³?+y³?+?+y??=(1+y+?+y³³)+(y³?+y³?+?+y??)-(1+y+?+y³³)
=(1+y+?+y??)-(1+y+?+y³³)=((y??-1)/(y-1))-((y³?-1)/(y-1))
Check: Evaluate ?_{i=34}??y^{i} = {
-((y³?)/(y-1))+((y??)/(y-1)) if y?1
44 if y=1
?
-((y³?)/(y-1))+((y??)/(y-1))=((y??-1)/(y-1))-((y³?-1)/(y-1)) is true
Using factoring:
y³?+y³?+?+y??=y³?(1+y+y²+?+y?³)=y³?(((y??-1)/(y-1)))
Check: Evaluate ?_{i=34}??y^{i}= {
-((y³?)/(y-1))+((y??)/(y-1)) if y?1
44 if y=1
?
-((y³?)/(y-1))+((y??)/(y-1))=y³?(((y??-1)/(y-1))) is false